Work Culture in Post-Pandemic: Role of the Temporal Flexibility and Supportive Supervisor Culture Towards Employee’s Work Stress - Gabriela Atalie; Alice Salendu (Universitas Muhammadiyah Surakarta, 2023)
Abstract. Although the Covid-19 Pandemic has abated, its effects thrive to impact other areas, including the workplace culture. Temporal Flexibility and Supportive Supervisor Culture are crucial for employees in the pandemic era, yet many contradictions remain in the research. Additionally, little is known about the relationship between Supportive Supervisor Culture and other work cultures under the pretext of employee work-life balance. This study aimed to evaluate the combination of two cultures modifying the work stress score among employees during the pandemic. The Experimental Vignette Method (EVM) was utilized through manipulation and surveys to acquire a more profound knowledge of worker stress levels. The results indicated that the group with a non-Temporal Flexibility Culture and a less Supportive Supervisor Culture reported the highest levels of work stress. Additionally, marital status governs stress levels; the amount of work stress among unmarried individuals was higher than among married adults with children. However, there was no significant contrast between job positions and employee status in terms of work stress mean. Moreover, younger employees were discovered to be more stressed at work than those of older employees. This research will assist organizations in adopting a culture that promotes the psychological well-being of their employees in the post-pandemic era.